3x(2x+20)=180

Simple and best practice solution for 3x(2x+20)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(2x+20)=180 equation:


Simplifying
3x(2x + 20) = 180

Reorder the terms:
3x(20 + 2x) = 180
(20 * 3x + 2x * 3x) = 180
(60x + 6x2) = 180

Solving
60x + 6x2 = 180

Solving for variable 'x'.

Reorder the terms:
-180 + 60x + 6x2 = 180 + -180

Combine like terms: 180 + -180 = 0
-180 + 60x + 6x2 = 0

Factor out the Greatest Common Factor (GCF), '6'.
6(-30 + 10x + x2) = 0

Ignore the factor 6.

Subproblem 1

Set the factor '(-30 + 10x + x2)' equal to zero and attempt to solve: Simplifying -30 + 10x + x2 = 0 Solving -30 + 10x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '30' to each side of the equation. -30 + 10x + 30 + x2 = 0 + 30 Reorder the terms: -30 + 30 + 10x + x2 = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 10x + x2 = 0 + 30 10x + x2 = 0 + 30 Combine like terms: 0 + 30 = 30 10x + x2 = 30 The x term is 10x. Take half its coefficient (5). Square it (25) and add it to both sides. Add '25' to each side of the equation. 10x + 25 + x2 = 30 + 25 Reorder the terms: 25 + 10x + x2 = 30 + 25 Combine like terms: 30 + 25 = 55 25 + 10x + x2 = 55 Factor a perfect square on the left side: (x + 5)(x + 5) = 55 Calculate the square root of the right side: 7.416198487 Break this problem into two subproblems by setting (x + 5) equal to 7.416198487 and -7.416198487.

Subproblem 1

x + 5 = 7.416198487 Simplifying x + 5 = 7.416198487 Reorder the terms: 5 + x = 7.416198487 Solving 5 + x = 7.416198487 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = 7.416198487 + -5 Combine like terms: 5 + -5 = 0 0 + x = 7.416198487 + -5 x = 7.416198487 + -5 Combine like terms: 7.416198487 + -5 = 2.416198487 x = 2.416198487 Simplifying x = 2.416198487

Subproblem 2

x + 5 = -7.416198487 Simplifying x + 5 = -7.416198487 Reorder the terms: 5 + x = -7.416198487 Solving 5 + x = -7.416198487 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + x = -7.416198487 + -5 Combine like terms: 5 + -5 = 0 0 + x = -7.416198487 + -5 x = -7.416198487 + -5 Combine like terms: -7.416198487 + -5 = -12.416198487 x = -12.416198487 Simplifying x = -12.416198487

Solution

The solution to the problem is based on the solutions from the subproblems. x = {2.416198487, -12.416198487}

Solution

x = {2.416198487, -12.416198487}

See similar equations:

| Y=4(-3x-3) | | 18x^6*(12x^2-24x)=0 | | Y=10x-4-6x+12 | | -2t+8=-t | | 18x^6*12x^2-24x=0 | | Y=5(3x-2) | | Y=8x+7+5x+3 | | 5x+4(2x+3)=x | | -10-2r=10+8r+10 | | (X^2+26x-39)=0 | | 5-7/2x | | A+B=74 | | 46+9x=146-3x | | 18-6n=3(2-n) | | f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 | | Y=-6/5x-3/5 | | 12x+10y=-6 | | (9/2)(-33/10) | | -2-2m=-9-m | | 10(1a+3b)=-20 | | -6+7q=5q | | x+3=2x+1-x+2 | | 8. 4m+5n=25 | | 3(2x+4)=-2(4x-13) | | 4x^3-3x=13 | | -8y-9=-10y+9 | | -3/2=-2/5y-5/3 | | 1-2x+3=2x+8 | | -3/2=2/5y-5/3 | | ax-b=c(x-a) |

Equations solver categories